Comparação da efetividade entre polietilenoglicol 4000 sem eletrólitos e hidróxido de magnésio no tratamento da constipação intestinal crônica funcional em crianças [ - Patricia Boechat Gomes (2009)
The aim of this study is to compare the effectiveness of two drugs: polyethylene glycol 4000 without electrolytes and Magnesium hydroxide. A randomized clinical trial was carried out for 6 months and the data was collected from July/2007 to November/2008 at University of Minas Gerais Medical School Clinical Hospital. The following variables were analyzed: stool consistency, frequency of bowel movements, improvement of signs and symptoms related to constipation (abdominal pain, straining, fecal incontinence) and medication compliance. The sample consisted of 38 children who were randomly assigned to either polyethylene glycol (17) or magnesium hydroxide (21). In the beginning of the study there was no significant difference between the two groups with regard to gender, age and presence of signs and symptoms related to constipation. Twenty-seven children completed the 6-month follow up, 15 in the group that received polyethylene glycol and 12 in the group that receivedmagnesium hydroxide. Medication compliance was significant higher (p < 0,05) among the patients who were under polyethylene glycol. There was improvement in all the analyzed variables, with no difference between the groups. This study shows that both laxatives were efficient for functional chronic constipation treatment. Polyethylene glycol proved to be a good therapeutic option due to its superior acceptance.